Toward an Adventist Theology of Social Witness: Covenant-keeping in the “Already-not yet" - Irizarry, Iriann (Kerygma, 2025)
This article explores selected implications of covenant-keeping for the church’s social witness within the theological framework of the “already-not yet” kingdom of God. Drawing on the work of Miroslav Volf and Matthew Croasmun, I maintain that the “already-not yet” theological framework both energizes and provides boundaries for the church as it embodies its witness regarding relevant contemporary social issues. This position will be enriched by selected supporting examples from conversation partners such as Padilla DeBorst (social marginalization and poverty), McCaulley (racial and ethnic discrimination), Volf (peacemaking and reconciliation), Richter (environmental stewardship), Yong (disability), and Swinton (mental health). Further, I will conclude that the social witness of the church should be central to the Adventist theological ethos in particular, rather than positioned at its margins or as a supplementary aspect. These insights aim to encourage the church to more fully embrace its role as a covenantal community in today’s social context.